Metaplastic breast carcinomas – analysis of prognostic factors in a case series - Nowara, Elżbieta; Drosik, Anna; Samborska-Plewicka, Marzenna; Nowara, Ewa Magdalena; Stanek-Widera, Agata (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Metaplastic breast carcinomas (MBC) are a rare group of cancers, accounting for about 1% of all breast cancers. The study presents a case series of MBC patients diagnosed, treated and followed up in one healthcare center. Material and methods : The study group comprised 18 women at the median age of 63 years. The most common carcinoma type in the study group was MBC with squamous epithelial differentiation (56%). Estrogen receptor expression was identified in one patient. No steroid or HER2 receptor expression was found in the remaining patients. We analyzed recurrence and survival rates in relation to clinical and therapeutic factors by using the Kaplan-Meier method. Results : A significantly longer overall survival time was noted among patients treated with adjuvant radiation therapy, p = 0.018. No other factors had a significant influence on survival. Because of the small size of the study group, results obtained in the study should be treated with caution.